Semantic Aspects of Spoken Interaction in the English Department at Bali Dwipa University: - , Ida Ayu Kade Dewi Artini; I Putu Eka Suardana; I Made Juliarta (Universitas Bali Dwipa, 2025)
This article, titled Semantic Aspects of Spoken Interaction in the English Department at Bali Dwipa University, investigates how meaning is constructed and conveyed through students’ everyday spoken communication. The main objective is to examine the semantic elements present in their conversations and to reveal the types of meaning relations that commonly appear in their speech. The data were obtained from spontaneous verbal exchanges among 20 undergraduate students (mean age = 20.8), all of whom were intermediate to advanced usersof English and agreed to participate in the study. To gather the data, the researcher employed a non-participant observational technique, supported by audio recordings and brief observational notes. The recorded interactions were later transcribed and examined using a qualitative descriptive framework that emphasized semantic relations, including sense–reference distinctions and lexical meaning patterns. The analysis showed that the most prominent semantic relations used by the students were synonymy, hyponymy, and polysemy. Additionally, many utterances relied heavily on shared situational knowledge, highlighting the significant role of contextual reference and pragmatic reasoning in maintaining smooth interaction. Overall, the study demonstrates that students’ spoken discourse is influenced by both their choice of semantic forms and the context in which these forms are used. These insights imply that incorporating semantic-focused learning activities may help students strengthen their communicative abilities and deepen their awareness of how meaning functions in actual spoken situations. The outcomes of this research can also assist lecturers in developing instructional strategies that draw attention to semantic aspects of spoken language.